Post- Civil War Developments in Nigeria: Issues, Challenges and the Establishment of NATSINTA Army Barracks, Katsina, 1970-2020 - Ali, Hannatu K.; Inuwa, Sadiq Tijjani (NIU Journal of Humanities; Vol 9 No 1 (2024): NIU Journal of Humanities, Vol. 9 No. 1, March 2024, 2024)
The paper examines the post-Nigerian Civil War developments that led to the establishment of Natsinta Army Barracks, Katsina.  Prior to 1966, the total strength of the Nigerian Army was merely 10,000. However, at the end of the war, the figure had risen to 250,000. This posed a serious challenge because the available barracks could not contain more than 10% of the personnel. In view of this, the Nigerian Army instructed the soldiers to leave the East because the region was saturated with artificial barracks. On the May 1, 1970 the 82-battalion arrived Katsina from Uli-Ahiala. They were accommodated at Sabongida, Gidan Kwakwa, Kayalwa, GRA and some hotels, as well as rented apartments in the city.  By 1977, the project for a permanent barracks was completed at Natsinta Village. The barracks housed the 82 battalion and in 1996 the 35 battalion replaced them. The scope of the paper is 1970-2020 because it was in 1970 that 82 battalion arrived Katsina. The year 2020 is the terminal end of the paper because it was in that year that residential quarters for the personnel of 17 brigade was constructed in the barracks. The paper argues that the establishment of the barrack was a landmark in the history of modern Katsina metropolis. Natsinta had impacts on the socio-economic and security aspect of Katsina. Primary and secondary sources of historical research were used in writing this paper. Keywords: Natsinta, Sabongida, Katsina, Army Barracks, Battalion, Civil war,